Parental genetic knowledge and attitudes toward childhood with genetic disorders - Alotaibi, Maha (Frontiers in Genetics, 2024)
Abstract Introduction Genetics' integration with society sparks a multifaceted exploration in medicine, ethics, and psychology. This survey probes parental perspectives on childhood genetic disorders, aiming to gauge their understanding, attitudes, and implications. It seeks to inform healthcare, counseling, and policy endeavors by uncovering gaps in knowledge and attitudes. Understanding the psychological impact and familial dynamics of genetic information underscores the need for tailored support services amidst rapid advancements in genetic technologies and their ethical complexities. Methodology It is a cross-sectional survey that assesses parental genetic knowledge and attitudes towards childhood genetic disorders. Data is collected by both paper and electronic formats. Data is cleaned in Excel and analyzed in IBM SPSS 29. Results Our study included 138 participants, predominantly female (71.7%), with mean age 36.01 years (SD=8.7). Most were Saudi (81.2%), with university education (65.9%). Notably, 73.2% reported consanguineous marriages. Regarding knowledge, 73.2% demonstrated good understanding of genetic disorders of child. Moreover, 47.8% and 34.1% claimed 40-60% and 34.1% knowledge levels, respectively. Doctors were the primary information source (79.7%). Participants expressed moderate impact of genetic disorders on their child's life (65.9%) and family dynamics (45.7%). Satisfaction with medical care was high (41.3% rated it as excellent). Challenges accessing healthcare were reported by 52.9%. Positive experiences with genetic disorders were reported by 62.3%, with male participants more likely to report positive experiences (B=0.888, p=0.041). Improvement areas included treatment availability (39.1%) and advanced medical tests (20.3%). Notably, informing relatives about the genetic disease significantly predicted positive attitudes (B=1.006, p=0.008). Overall, obtaining information from doctors significantly enhanced knowledge (B=2.296, p=0.024). Conclusion Our study shows significant associations between parental knowledge, attitudes towards genetic disorders, and healthcare experiences. It underscores the importance of informed decision-making and targeted interventions to address challenges and improve outcomes in managing childhood genetic disorders.